2004
DOI: 10.1074/jbc.m404899200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dynamin-associating Molecule, Formin-binding Protein 17, Induces Tubular Membrane Invaginations and Participates in Endocytosis

Abstract: Dynamin associates with a variety of SH3 domaincontaining molecules via a C-terminal proline-rich motif and takes part, with them, in endocytic processes. Here, we have investigated a new dynamin-associating molecule, formin-binding protein 17 (FBP17), involved in deforming the plasma membrane and in endocytosis. FBP17 formed tubular invaginations originating from the plasma membrane. Its N-terminal Fer/CIP4 homology domain, a coiled-coil domain, and a proline-rich motif were required for tubular invagination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
112
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 34 publications
(39 reference statements)
8
112
0
Order By: Relevance
“…Overexpression of Toca-1L induced plasma membrane invagination (Fig. 5, A and C), which is similar to what was observed by overexpression of Rapostlin (7)(8)(9). Overexpression of Toca-1S induced membrane invagination to a lower extent (Fig.…”
Section: Overexpressed Toca-1 Suppresses Neurite Elongation Of Pc12 Csupporting
confidence: 70%
See 2 more Smart Citations
“…Overexpression of Toca-1L induced plasma membrane invagination (Fig. 5, A and C), which is similar to what was observed by overexpression of Rapostlin (7)(8)(9). Overexpression of Toca-1S induced membrane invagination to a lower extent (Fig.…”
Section: Overexpressed Toca-1 Suppresses Neurite Elongation Of Pc12 Csupporting
confidence: 70%
“…inating Property-PCH family proteins, when expressed at higher levels, induce tubular plasma membrane invagination through the N-terminal F-BAR/EFC domain (7)(8)(9). To examine whether Toca-1 induces plasma membrane invagination in living cells, we transiently transfected EGFP-tagged wild-type Toca-1, or Toca-1 mutant in HeLa cells (Fig.…”
Section: Overexpressed Toca-1 Suppresses Neurite Elongation Of Pc12 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, FBP17 (formin-binding protein 17) has been shown to interact with dynamin and to regulate endocytosis by forming vesicotubular structures (31). PSTPIP, on the other hand, is involved in actin polymerization (32), a process known to be important for endocytosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…F-BAR or EFC domains (9,13) were identified from a group of proteins known as Pombe Cds15 homology proteins (25,26) that are involved in various actin-related processes, including clathrin-mediated endocytosis. F-BAR domains, like N-BAR domains, bind anionic lipids and induce vesicle tubulation in vitro (16,27) and cause tubulation of plasma membrane when overexpressed in mammalian cells (16,27,28). Crystal structures of F-BAR domains of FBP17 and CIP4 showed that they also form a crescent-like dimer but that their intrinsic curvature is smaller than that of dAmp-BAR (29).…”
mentioning
confidence: 99%